Retrospective assessment of lesser prairie-chicken habitat in the Sand Sagebrush Prairie Ecoregion - Vhay, Megan Patricia (Kansas State University, 2022)
Populations of lesser prairie-chickens (Tympanuchus pallidicinctus) in the Sand Sagebrush Prairie Ecoregion of southwest Kansas and southeast Colorado, USA, have declined sharply since the mid-1980s. Decreased habitat quality and availability are believed to be the main drivers of declines; however, no broad-scale assessment of habitat change has been conducted for the ecoregion. My objectives were to reconstruct landscape-scale change in the ecoregion since 1985, assess changes in vegetation structure and composition relative to management goals, and compare features of Conservation Reserve Program (CRP) grasslands used and apparently unused by lesser prairie-chickens. I assessed change in landcover types and calculated landscape metrics using Land Change Monitoring, Assessment, and Projection (LCMAP) layers, and documented presence of anthropogenic structures including oil wells and transmission lines. I compared historical and contemporary fine-scale vegetation composition and structure survey data from public lands. I also tested for differences in landscape-scale and field-scale characteristics between CRP with tagged bird locations and those without. Landcover type composition and tree occurrence changed little since 1990 across the Sand Sagebrush Prairie Ecoregion. However, anthropogenic structures (i.e., oil/gas wells, cell towers, wind farms, and transmission lines) increased, potentially causing functional habitat loss as a result of avoidance by lesser prairie-chickens. Quality vegetation structure has declined on Comanche National Grassland since 1985. Used CRP fields were closer to release sites of translocated lesser prairie-chickens than apparently unused CRP, with a greater proportion of used fields associated with ≥60% grassland. Increased anthropogenic structures and decrease in vegetation vertical structure appears to have decreased habitat as well as the quality of existing habitat for lesser prairie-chickens, likely contributing to recent population declines throughout the Sand Sagebrush Prairie Ecoregion. Tracts of CRP associated with ≥60% grassland within 5km may continue to provide habitat for lesser prairie-chickens, but is a precarious option for habitat conservation in a trend of declining CRP enrollment. If lesser prairie-chickens are still considered a management priority by the U.S. Forest Service, the Cimarron and Comanche National Grasslands will need to adjust management practices to promote habitat conditions that support lesser prairie-chicken populations.
Keywords: Lesser prairie-chicken; Habitat